PENGARUH KONSENTRASI PUPUK ORGANIK CAIR SERTA VARIETAS DAN GALUR TERHADAP PERTUMBUHAN DAN PRODUKSI BENIH TANAMAN KACANG PANJANG (Vigna sinensis (L.) Savi ex Hassk.) - Arnandha Desya Refaldi; Prasodjo Soedomo; Muharam Muharam; Yayu Sri Rahayu (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2021)
Long bean production in Indonesia continues to decline every year, this is due to land conversion and the lack of application of agricultural technology. One of the efforts to increase long bean production is by multiplying quality seeds using organic materials as nutrients needed by plants. This study aims to determine the response of the growth and production of long bean seeds to the interaction of strains, varieties with a concentration of liquid organic fertilizer. The research was conducted at the Vegetable Crops Research Institute, Lembang, West Bandung Regency from July 2020 to January 2021. The research method used was an experimental method with a Randomized Block Design (RBD) with a split-plot design consisting of 2 factors: the first factor (main plot) (A) was the variety and strain with 2 levels, a1 (Tavi canton variety) and a2 (pras-1 strain).The second factor (subplot) (B) is concentration of biopras-1 with 5 levels, b1 (0 cc/l-1 water), b2 (1 cc/l-1 water), b3 (2 cc/l-1 water), b4 (3 cc/l-1 water) and b5 (4 cc/l-1 water). The effect of the treatment was analyzed by means of variance and if the f test at 5% level was significantly different, then to find out the best treatment was continued with the DMRT (Duncan Multiple Range Test) at the 5% level. The results showed that there was an interaction between varieties, lines with various concentrations of biopras-1 liquid organic fertilizer on dry seed weight per plant, dry seed weight per plot, and 1000 seeds weight. Treatment of pras-1 lines with the concentration of liquid organic fertilizer biopras-1 4 cc / l of water was able to give the best results on dry seed weight per plant (35.31 gr), dry seed weight per plot (1.298.20 gr or 2.16 Ton/ha-1) and the weight of 1000 seeds (153.10 gr).